The Impact of Digital Literacy, Income, and Financial Literacy on Investment Choices with Financial Behavior as a Mediating Factor Among Healthcare Professionals in Berau Regency - Kushardono, Lucky; Bayu, Muhammad; Muslimin, Muslimin; Rudianto, Pandef (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
In the digital age, healthcare professionals are required to possess not only healthcare competencies but also financial and digital literacy to support better financial management and investment decision-making. Unhealthy financial behaviors, such as excessive spending and minimal allocation of funds for investment, are major obstacles. Additionally, low skills in utilizing digital platforms increase the risk of becoming a victim of fraudulent investments. This research aims to address this phenomenon by studying healthcare workers in Berau Regency, using the Structural Equation Modeling (SEM) approach. The research findings indicate that financial literacy does not directly influence the financial behavior of healthcare workers. Conversely, digital literacy and income have a positive and significant influence on financial behavior. Research has proven that favorable financial behavior not only enhances investment decision-making ability but also significantly mediates the influence of digital literacy and income on investment decisions. Financial literacy also has a positive direct impact on investment decisions, but this influence is not mediated by financial behavior, while digital literacy does not have a direct impact on investment decisions. Revenue plays an important role in supporting optimal and sustainable investment decisions. This finding provides a basis for the government and the Berau District Health Office to design financial and digital literacy education programs. Furthermore, this study's findings offer valuable insights to healthcare professionals about managing income and making investments that promote long-term well-being.